Novel luminescent probes for nucleic acids on base of cyanine dye excimers - Filimonova, I. I.; Sorokin, A. V.; Кurilchenko, I. Yu.; Yefimova, S. L.; Borovoy, I. A.; Malyukin, Yu. V. (Biophysical Bulletin, 2009)
Using optical spectroscopy methods features of interaction of oxacarbocyanine dye derivatives (C2, C6, and C9), which differ only by hydrocarbon tails length, with nucleic acids (DNA and RNA) have been investigated. It has been found that the C2 dye almost not interact with the NA, whereas the C9 dye reveals a strong interaction with non-luminescent dimers formation. Contrary, the C6 dye interacts with NA and forms excimers, in which the luminescent band is shifted on 150 nm into a long wavelength side compare to an absorption band. It has been shown that the C6 excimer formation is specific for interaction with NA and it isn’t observed at the dye interaction with another type of biological object. Therefore, the C6 dye is proposed as a new specific luminescent probe for nucleic acids.